Multigravida at 31 Weeks with Imminent Preterm Labor, Type 2 Diabetes Mellitus, Maxillary Abscess, and Bad Obstetric History : A Case Report - Sentani, Ray Suga Aulia; Bernolian, Nuswil; Muzakkie, Mufida; Kusnadi, Yulianto (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Imminent preterm labor (IPL) is defined by irregular uterine contractions, back pain, and vaginal discharge, with approximately 25-30% of cases progressing to preterm delivery. Preterm birth remains a major global issue, contributing to 35% of neonatal deaths, and often results in long-term health complications for the infant. This case report discusses a 35-year-old woman (G4P2A1) at 30 weeks of gestation, with a history of type 2 diabetes mellitus (T2DM), bad obstetric history (BOH), and a right maxillary abscess. She presented with swelling and pus discharge from the maxillary region, along with abdominal cramps, but no signs of imminent labor. The patient’s diabetes was managed with insulin, and her clinical condition was complicated by high blood glucose and an ongoing infection. The cervical length was measured via ultrasound, which indicated a risk for preterm delivery, and the patient was diagnosed with IPL. Initial management included fluid resuscitation, tocolytics to prevent labor, and antibiotics for the maxillary abscess. The patient was closely monitored, and insulin therapy was adjusted to stabilize glucose levels. Despite the complexity of managing IPL in diabetic patients, the patient's condition improved after debridement of the abscess and management of blood glucose levels. This case emphasizes the importance of multidisciplinary care in managing complicated pregnancies with comorbidities like T2DM.